2020
DOI: 10.1177/2277977920959583
|View full text |Cite
|
Sign up to set email alerts
|

Dr. Reddy’s Laboratories Ltd: Searching Its Glorious Days

Abstract: This case explores the phenomenon of organization decline and the dilemma around the different paths that may be traversed by Dr. Reddy’s Laboratories Ltd. There are multiple theories of organizational decline, and mostly they encompass both the external environment and the internal aspects of the firm, including the context of decision-making. Moreover, the organization decline-and-turnaround model highlights the different causes of decline, response factor, firm action and outcomes in a unified and comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…The research byAbraham and Kumar (2020),Balgobin and Pandit (2001),Kailasam and Wongsurawat (2016), Pai (2015), Patnaik (2014), Roy and Bhattacharya (2011), and TenBrink et al (2018) indicate that cost retrenchment has shown to assist successful turnarounds. Gupta and Wang (2004), Pai (2015), and Patnaik (2014) indicate that restructuring by outsourcing to low-cost locations helps with successful turnarounds.…”
mentioning
confidence: 99%
“…The research byAbraham and Kumar (2020),Balgobin and Pandit (2001),Kailasam and Wongsurawat (2016), Pai (2015), Patnaik (2014), Roy and Bhattacharya (2011), and TenBrink et al (2018) indicate that cost retrenchment has shown to assist successful turnarounds. Gupta and Wang (2004), Pai (2015), and Patnaik (2014) indicate that restructuring by outsourcing to low-cost locations helps with successful turnarounds.…”
mentioning
confidence: 99%